Road Safety Perception of Different Types of Drivers in Egypt - Aya Raafat Salama; Prof. Mona H. M. Abd-Allah; Dr. Mohamed Shawky, (Indian Journal of Transport Engineering (IJTE), 2023)
The present research examined the variation in driving behaviors among drivers of different types of vehicles in Egypt. Three categories of drivers have been investigated: private car drivers, microbus drivers, and motorcyclists. A customized version of the Manchester Driver Behavior Questionnaire (DBQ) was developed for the data collection process. An exploratory factor analysis (EFA) was applied to the questionnaire data to determine the underlying factors within the set of behavioral items. The EFA has helped identify three robust factors: Errors, Positive Behaviors, and Violations, respectively, within the responses of drivers.Multiple regression analyses were carried out to establish which socio-demographic variables are the best predictors of each of the three deduced factors. One-way ANOVA tests were then conducted to analyze the differences among the three drivers categories in terms of the three EFA factors as well as the history of crashes and violations. It was found that microbus drivers committed a significantly higher number of traffic violations than both motorcyclists and private car drivers. Also, private car drivers were involved in a fewer number of crashes and had more positive driving behavior compared to microbus drivers. The research findings would aid in targeting the high-risk drivers in future road safety educational campaigns and training courses.